Oxidative Stress in Pre-Eclampsia: Bibliometric Visualization Studies and Analysis - Sri Wahyuni, Endang; Wiyono, Nanang; Maryatun, Maryatun; Nurul Mahmudah, Irvina; Duwi Handayani, Juleha; Lutfatul Jannah, Safella (STIKES Mamba'ul 'Ulum Surakarta, 2025)
Background: Preeclampsia is a major cause of death and maternal health problems in the world. Preeclampsia can be triggered by an increase in free radicals which cause oxidative stress. Aim: This study aimed to visually map research publications on the mechanisms of oxidative stress in preeclampsia based on bibliometric analysis. Methods: Systematic Literature Review research design with bibliometric analysis. VOSviewer, Publish or Perish (PoP), and Microsoft Excel resources were used. The database was retrieved from Scopus using the keywords: preeclampsia AND